Environmental Dimension and Managerial Factors of the Product Development Process - Kawamoto, Caroline Izumi; Santos, Fernando César Almada; Jabbour, Charbel José Chiappetta (Revista Gestão da Produção Operações e Sistemas, 2007)
The objective of this article is to study how the performance determining managerial factors of the product development process (PDP) change in function of the insertion of the environmental variable in the organizational context. Managerial factors were researched in the literature pursuant to theme that influence process performance, such as the integration of PDP to company strategies, the integration of the companys functional areas, the role of project leaders, development, involvement of the supplier and client chain, structuring of process phases and activities and a broad analysis of the product development process. Based on the original approach of these factors, and considering the environmental dimension, the main changes in the product development process were systematized. Most especially, the authors focused on analyzing the PDP structure with the insertion of the environmental variable and utilization of environmental tools and methodologies. In conclusion, the need to continue the theoretical study and carry out field research to explore how the managerial factors determine the full insertion of the environmental dimension in PDP was verified. Keywords: Product development process; Managerial factors, Environmental variable; Environmental tools and methodologies.